Hierarchical shell-core structures of concave spherical NiO nanospines@carbon for high performance supercapacitor electrodes. (20th January 2019) - Liu, Panbo; Yang, Mengying; Zhou, Suhua; Huang, Ying; Zhu, Yade
Abstract: The inherent electrochemical performance of supercapacitor electrodes is highly depends on their structures, therefore, numerous efforts are focus on rationally designing and constructing supercapacitor electrodes with hierarchical structures. In this work, we report a facile method for controllable synthesis of hierarchical shell-core structures by anchoring NiO nanospines on concave spherical carbon particles. It is observed that the inner carbon core, acting as a highly efficient current collector, is inherited from the calcination of concave spherical sulfonated polystyrene, while the external shell, resulting from these NiO nanospines, plays the role of active materials. Benefiting from the hierarchical shell-core structures with large specific surface area, additional electroactive sites, reduced interior space, short ions diffusion pathway and intimate electrode/electrolyte contacts, the as-synthesized electrodes exhibit superior electrochemical performance, such as high specific capacitance (1161 F g −1 at a current density of 2 A g −1 ), good rate capability (839 F g −1 at a high current density of 10 A g −1 ) as well as long cycling stability (92.4% retention after 3000 cycles at 2 A g −1 ). We believe that the electrodes are expected to be the most promising candidate for supercapacitors, and more importantly, this strategy plays an important role in the construction of novel hierarchical shell-core structures with superior electrochemical performance for advanced energy storage materials.